Muffled voices: yaoi manga as mediation of feminine discourse - Gláucio Aranha (Galáxia, 2010)
Manga is a textual model originated in Japan which has been occupying increase space in occidental media. In the mid-80’s the first yaoi manga appeared. Initially, this shojo manga subgenus was drawn, written and published by manga’s fans as a satire on the masculine hegemony in this media. The receptivity of feminine audience contributed to yaoi`s consolidation as a media “written by women for women”. Its main specificity is the theme: romance between men. The use of masculine homoerotism as a feminine expression subverts the social hierarchies of a society marked by machismo. Japanese women have been using the homoerotic romance as a expressive space for their oppressed voices, relying on hierarchical equality between partners.